Modern role of assessment as a factor of full-functioning land market in Ukraine - Koshel, A. (Land Management, Cadastre and Land Monitoring, 2020)
The current state of the market of non-agricultural land and agricultural land that are not under the moratorium is analyzed. The legislatively fixed definition of monetary valuation, which is one of the bases for opening the land circulation of commodity agricultural production, is investigated. The main features of land valuation for which the process of land valuation should be conducted in terms of market relations are noted. The disadvantages of the existing system of regulatory monetary valuation of agricultural land outside the settlements of Ukraine, which are formed not on the market valuation, are presented. The method of group estimation of land according to the common characteristics of land on a market basis, which is used in most countries of the world and is called mass estimation, is proposed. Advantages and disadvantages of methods of mass land valuation are shown in the conditions of expectation of opening of a complete land market. The directions of improvement of the modern system of land valuation for the purposes of their taxation and determination of real value are determined. The extreme importance of land valuation as the main regulatory factor for the proper functioning of the land market is shown. Keywords: land market, valuation, regulatory monetary valuation, market price, mass valuation, land taxation.